Unveiling the Role of Guanidinium for Enhanced Charge Extraction in Inverted Perovskite Solar Cells - Xu, Weidong; Min, Ganghong; Utama Kosasih, Felix; Dong, Yueyao; Ge, Ziyuan; Gu, Qichun; Chen, Muzi; Pacalaj, Richard A.; Wang, Tong; Webb, Thomas; Du, Tian; Righetto, Marcello; et al. (ACS Energy Letters, 2025)
The incorporation of guanidinium (Gua) cations has significantly enhanced the optoelectronic properties of various perovskite compositions. When combined with other A-site cations in perovskite solar cells (PSCs), Gua cations not only enhance the power conversion efficiency of the solar cells but often improve their overall stability. While most studies examining the impact of Gua focus on PSCs with the n-i-p (conventional) structure, fewer have investigated its effects on the mechanism and performance of the p-i-n (inverted) structure. We investigate how partially substituting A-site cations with Gua affects the performance of PSCs and the associated charge carrier dynamics. Enhanced performance is observed in Gua-substituted inverted PSCs, primarily due to improved short-circuit current density and fill factor values. Our spectroscopic and microscopic analyses reveal that these enhancements stem from accelerated charge transport within the perovskite layer combined with inhibited ion migration following Gua incorporation, attributed to the reduction of localized inhomogeneities, which also notably enhance device stability. Our findings elucidate the role of Gua in inverted PSCs, showing negligible impact on open-circuit voltage but significant improvement in charge extraction efficiency. This contrasts with previous reports on conventional structures, where performance enhancement is primarily attributed to trap state reduction, resulting in higher open-circuit voltage.
CRIS-Team Scopus Importer:2025-05-23